Corrosion Inhibition of Mild Steel by Ecofriendly Extract of Croton sparciflorus - KASTHURI*, P.K.; ARULANANTHAM†, A. (Asian Journal of Chemistry, 2009)
The acid extract of Croton sparciflorus containing bio active ingredients have been used as corrosion inhibitor for mild steel in 1 M HCl. The inhibitor efficiency calculated using weight loss, potentio-dynamic polarization and impedance methods has been found to be effective inhibitor. The effect of temperature on the corrosion behaviour of mild steel indicated that inhibition increased with increasing temperature. It follows Temkin adsorption isotherm. Polarization and impedance studies revealed that the inhibitor was mixed type and may form a complex with the metal surface.